The Effectiveness of English Animation Movie Toward Students’ Writing Descriptive Text at Eight Grade of Smpit Al-Mubarok Serang - Khaerunnisa Khaerunnisa; Rita Handayani; Ledy Nurlely (Departement of Mathematics Education, 2024)
The goal of this research is to obtain empirical data about the effectiveness of English animation movie toward students’ writing text. To achieve that goal, this research used a quasi-experimental design involving eight grade of SMPIT Al-Mubarok Serang. The population Used was 110 students. The sample consist of 20 students from experimental class and 20 students’ control class which are selected using cluster random sampling. Moreover, the result of the post-test revealed that the experimental class was a significantly higher score than the control class. In addition, the result of the Independent Sample T-Test revealed that the sig-2 tailed value 0.00<0.05. This is also supported by the results of Effect Size test which has value 3.24 and the category was strong effect (significant). Therefore it was proven that the use of animation movie was effective toward students’ writing of descriptive text at eight grade of SMPIT Al-Mubarok in the academic year 2023/2024. Thus, the use of animation movie is suggested toward students’ writing of descriptive text.